El concepto de riesgo y los delitos anticipatorios. Una aproximación acerca de una distinción necesaria - Beade, Gustavo A. (Nómadas. Critical Journal of Social and Juridical Sciences, 2008)
The proposal of the present work, is to try to defend the idea that the central criterion in a preventive theory of punishment, would have to be tie only with the type of risk that the actions imply, like thus also the danger degree that could generate to the elements that the Criminal Law tries to protect. It is tried to maintain that a preventive theory, would have to carry out only valuations ex-ante, it against the establishment of the results, which supposes a valuation ex-post, that differs from the originally propose of Criminal Law, this is the prevention. Thus, the objective of this work is to carry out, to the light of the enunciated principle, a consistent formulation with the so calls risk harms (or remote harms). One will be to determine which of these remote harms must be accepted, and as they imply an advance of the State on the individuals, by means of the exigency of certain behaviors (in some cases virtuous) from these. The intention of this work is to be able to establish a differentiating criterion, that allows to determine which of these remote harms must be agreed and which import the State intervention in own and exclusive spheres of the individuals.